PENGARUH TEKANAN, KESEMPATAN DAN RASIONALISASI TERHADAP PERILAKU KECURANGAN AKADEMIK PADA PEMBELAJARAN DARING - Fadhilah, Farah; Farina, Khorina (LPPM Universitas Bina Bangsa, 2025)
The purpose of this study was to examine the effect of pressure, opportunity and rationalization on academic cheating behavior. This type of research uses a quantitative method. The population in this study were active students of the employee class of the Faculty of Economics and Business, Trilogi University who participated in online learning. The sampling method used in this study was convenience sampling with a sample size of 135 respondents, the type of data in this study was primary using a questionnaire. The analysis used in this study was descriptive analysis and Partial Least Square (PLS) using SmartPLS 4. The results of this study indicate that pressure and opportunity do not affect academic cheating behavior in online learning, but rationalization has a positive and significant effect on academic cheating behavior in online learning